2017
DOI: 10.3389/fphar.2017.00435
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships of Pentacyclic Triterpenoids as Potent and Selective Inhibitors against Human Carboxylesterase 1

Abstract: Human carboxylesterase 1 (hCE1), one of the most important serine hydrolases distributed in liver and adipocytes, plays key roles in endobiotic homeostasis and xenobiotic metabolism. This study aimed to find potent and selective inhibitors against hCE1 from phytochemicals and their derivatives. To this end, a series of natural triterpenoids were collected and their inhibitory effects against human carboxylesterases (hCEs) were assayed using D-Luciferin methyl ester (DME) and 6,8-dichloro-9,9-dimethyl-7-oxo-7,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…In a previous study, hCEs had been shown to be involved in aspirin hydrolysis [ 22 ]. Recent reports have revealed that many natural triterpenoids were found to display the inhibitory effects on hCEs [ 32 , 33 , 34 ]. A Master dissertation also reported that gensenosides exhibited the inhibition effect toward hCEs [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, hCEs had been shown to be involved in aspirin hydrolysis [ 22 ]. Recent reports have revealed that many natural triterpenoids were found to display the inhibitory effects on hCEs [ 32 , 33 , 34 ]. A Master dissertation also reported that gensenosides exhibited the inhibition effect toward hCEs [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, their use against molecular targets has diminished over the past two decades, due to the technical barriers to screening natural products 95 . Zou et al 96 , 97 have collected a series of natural triterpenoids and characterized their inhibitory effects against CES using DME (D-luciferin methyl ester, a probe for CES1) and DDAB (6,8-dichloro-9,9-dimethyl-7-oxo-7,9-dihydroacridin-2-yl benzoate, a probe for CES2) as the specific substrates for high-throughput screening of inhibitors against CES1 and CES2, respectively. Two pentacyclic triterpenoids, ursolic acid (UA) and oleanolic acid (OA), exhibited strong inhibitory effects on CES1 ( Fig.…”
Section: Ces Inhibitorsmentioning
confidence: 99%
“…Human carboxylesterase 1 (hCE1), a serine hydrolase distributed in liver and adipocytes, is highly associated with type 2 diabetes and hypertriglyceridemia [90]. It was reported that UNA displayed strong inhibitory activity against hCE1 (IC 50 = 0.037 µM), and this effect was more powerful than the activity of ULA (IC 50 = 0.24 µM) [90].…”
Section: Other Expected Therapeutic Potentialmentioning
confidence: 99%